2013
DOI: 10.1016/j.ejphar.2012.11.051
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin may promote mitochondrial biogenesis via the production of hydrogen peroxide and the induction of Sirtuin1/PGC-1α genes

Abstract: Based on the rapid hydrolysis of acetyl salicylic acid (ASA, Aspirin) to salicylic acid (SA), the ability of SA to form dihydroxy benzoic acid (DBA), and the latter’s redox reactions to yield hydrogen peroxide (H2O2), we predicted that ASA may have the potential to induce Sirtuin1 (Sirt1) and its downstream effects. We observed that treatment of cultured liver cells with ASA resulted in the induction of Sirt1, peroxisome proliferator-activated receptor-gamma co-activator-1α (PGC-1α), and NAD(P)H quinone oxidor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 36 publications
2
20
0
Order By: Relevance
“…The concentration of H 2 O 2 affects mitochondrial biogenesis and enzyme activity. Modest induction of H 2 O 2 has been shown to promote mitochondrial biogenesis (Kamble et al 2013;Park et al 2013), while a large concentration of H 2 O 2 induces apoptosis, decreases mitochondrial enzyme activity, and leads to cardiac dysfunction (Le on et al 2007;Raisanen et al 1999). These results suggest that maternal exercise may lead to increased efficiency of mitochondria in the fetal hearts of their offspring.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of H 2 O 2 affects mitochondrial biogenesis and enzyme activity. Modest induction of H 2 O 2 has been shown to promote mitochondrial biogenesis (Kamble et al 2013;Park et al 2013), while a large concentration of H 2 O 2 induces apoptosis, decreases mitochondrial enzyme activity, and leads to cardiac dysfunction (Le on et al 2007;Raisanen et al 1999). These results suggest that maternal exercise may lead to increased efficiency of mitochondria in the fetal hearts of their offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms invoked to explain the benefits of salicylates include increased mitochondrial biogenesis and increased mitochondrial energy metabolism via activation of key metabolic regulators such as AMP-activated protein kinase (AMPK), NF-Kb, and SIRT1, among others [48]. However, these findings contradict an older literature from the 1970s and 1980s that focused on the link between aspirin and Reye Syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, mitochondrial superoxide production was found to increase the longevity of nematodes by triggering ROS-scavenging responses [25]. It has been recently indicated that aspirin promotes mitochondrial biogenesis through H 2 O 2 production and SIRT1/PGC-1α induction in cultured mouse liver cells [26]. A most new report has also demonstrated that H 2 O 2 enables the up-regulation of mitochondria-specific SIRT3 and Mn-SOD in mice [27].…”
Section: Discussionmentioning
confidence: 99%